Eating together : food, friendship, and inequality - Julier, Alice P. (University of Illinois Press, 2013)
"Sharing and enjoying food together is a basic human expression of friendship, pleasure, and community, and in Eating Together: Food, Friendship, and Inequality, sociologist Alice P. Julier argues that the ways in which Americans eat together play a central role in social life in the United States. Focusing on the experiences of African American and non-ethnic white hosts and guests, she explores the concrete pleasures of cooking as well as the discourses of food and sociability that shape the experience of shared meals. Delving into a wide range of research, Julier analyzes etiquette and entertaining books from the past century and conducts interviews and observations of dozens of dinner parties, potlucks, and buffets. She finds that when people invite friends, neighbors, or family members to share meals within their households, social inequalities involving race, economics, and gender reveal themselves in interesting ways: relationships are defined, boundaries of intimacy or distance are set, and people find themselves either excluded or included. An insightful map of the landscape of social meals, Eating Together shows how and why people will go to considerable effort, even when resources are limited, to ensure that they continue to eat together with friends throughout their lifetimes."--Publisher's description.